Kinematics Analysis of the 3-PRS Parallel Mechanism - Chen Chun; Wang Qingliang; Huang Yumei; Cheng Xiang (Jixie chuandong)
For the reason that the position solution of a parallel mechanism is hard to be solved directly,the solution of positive position are parsed by the method of transformation to solve object location based on the solved inverse position solution in the 3- PRS parallel mechanism,and the velocity and acceleration of the passive joints are obtained by the D’Alembert principle,which can avoid the complexity of the direct derivation on the spatial mechanism. Through the analysis of an actual 3- PRS parallel mechanism instance,the results show that the method of objects transformation is simple and effective for solving the position positive solution of the parallel mechanism. At the same time,it is pointed out that the derived movements also exist besides the main three motions of 3- PRS parallel mechanism,this reveals that the derived kinematics must be taken into account in actual usage.